Malignant Hyperthermia – an Update for Perioperative Nurses - Riazi, Sheila; Brandom, Barbara (Operating Room Nurses Association of Canada Journal, 2015)
This article is a summary of the “Updates on Malignant Hyperthermia” presentation given at the 2015 ORNAC National Conference in Edmonton. It presents the facts known about malignant hyperthermia (MH) including definition, anesthetic and non-anesthetic triggers for MH, signs and symptoms, and treatment of MH. It also discusses the care of an MH susceptible patient while undergoing an elective surgery.